Cultural Ecosystem Services and the Challenge for Cultural Geography. Issue 10 (October 2014) - Leyshon, Catherine
Abstract Cultural ecosystem services are one of four services identified by the Millennium Ecosystem Assessment as critical to the support of human life on earth and therefore in need of proper valuation and protection. Cultural services seem to embody the objects of enquiry for cultural geographers interested in landscape, identity and place. However, potentially insurmountable epistemological challenges face the participation of cultural geographers in the following: (i) the identification and evaluation of CES; and (ii) the operationalisation of environmental governance. One challenge for cultural geographers is to make the relevance of their theoretical and conceptual insights felt in a field dominated by the natural sciences and scientific epistemologies. Meanwhile, the problems of defining and identifying cultural services in ways that make them compatible with provision, regulating and supporting services, even threaten the continued inclusion of cultural services in the ecosystem services approach. The concept of landscape seems to provide a shared intellectual terrain over which cultural geographers can work with others interested in cultural ecosystem services.